A guard to reduce the accidental oxidation of PbTe nanocrystals. Issue 26 (27th June 2018) - Liu, Gang; Yan, Cong; Xue, Zhen-Jie; Liu, Cong; Xu, Guiying; Wang, Tie
Abstract : Benzene derivatives can reduce unexpected PbTe NCs oxidation even with the introduction of leaked air or moisture during the synthesis procedure. Abstract : In the synthesis of lead telluride nanocrystals (PbTe NCs), oxidized PbTe is commonly regarded as a waste material as this will reduce the performance of pure PbTe NCs. The waste is normally thrown away, leading to potential environment risks and is less economical in terms of atom usage. Conventional anti-oxidation methods such as inert gas flow or sealed systems cannot deal with leaking or accidental contamination. To solve this problem, by simulating accidental oxidation, we utilized a cheap and easily-performed strategy to reduce the oxidation to a very low level. Further analysis indicates that this anti-oxidation effect should be due to interactions between the double bonds from the coating ligands and the extended π bonds from the benzene rings. This strategy increases the synthesis efficiency of the reactants and reduces the environmental pollution risk.